A randomized controlled trial to compare two methods of constraint-induced movement therapy to improve functional ability in the affected upper limb in pre-school children with hemiplegic cerebral palsy: CATCH TRIAL. (July 2018) - Christmas, Pauline M; Sackley, Catherine; Feltham, Max G; Cummins, Carole
Objective: To determine the feasibility and short-term efficacy of caregiver-directed constraint-induced movement therapy to improve upper limb function in young children with hemiplegic cerebral palsy. Design: Randomized controlled trial with masked assessment. Setting: Community paediatric therapy services. Subjects: Pre-school children with hemiplegic cerebral palsy. Interventions: Caregiver-directed constraint-induced movement therapy administered using either 24-hour short-arm restraint device (prolonged) or intermittent holding restraint during therapy (manual). Main measures: Primary measures include Assisting Hand Assessment (AHA) at 10 weeks. Secondary measures include adverse events, Quality of Upper Extremity Skills Test and Pediatric Quality of Life Inventory. Feasibility measures include recruitment, retention, data completeness and adherence. Results: About 62/81 (72%) of eligible patients in 16 centres were randomized (prolonged restraint n = 30; manual restraint n = 32) with 97% retention at 10 weeks. The mean change at 10 weeks on the AHA logit-based 0–100 unit was 9.0 (95% confidence interval (CI): 5.7, 12.4; P < 0.001) for prolonged restraint and 5.3 (95% CI: 1.3, 9.4; P = 0.01) for manual restraint with a mean group difference of 3.7 (95% CI: −1.5, 8.8; P = 0.156) (AHA smallest detectable difference = 5 units). No serious related adverse events were reported. There were no differences in secondary outcomes. More daily therapy was delivered with prolonged restraint (60 vs 30 minutes; P < 0.001). AHA data were complete at baseline and 10 weeks. Conclusion: Caregiver-directed constraint-induced movement therapy is feasible and associated with improvement in upper limb function at 10 weeks. More therapy was delivered with prolonged than with manual restraint, warranting further testing of this intervention in a longer term trial.